Structural Performance and Finite Element Modeling of Roller Compacted Concrete Dams: A Review - Habib, Ahed; AL Houri, Ausamah; Habib, Maan; Elzokra, Ahmed; Yildirim, Umut (Latin Amer J Solids Structures, 2021)
There is no doubt that concrete is one of the most consumed materials all over the world. It is a composite mix widely used for constructing structures and infrastructures to sustain environmentally induced stresses such as thermal and seismic. As the mainstream of construction industry is tended to find out feasible solutions, Roller Compacted Concrete (RCC) was introduced to play an essential role in the development of dams and pavements, where over 550 RCC dams were created by the end of 2012. In fact, this material has the same basic constituents of conventional concrete with a zero-slump and a significant difference in the placing process. The majority of available studies in the literature are composed of numerical investigations to assess the thermal and seismic behavior of RCC dams and to provide a clear view on how to improve its performance under various loading conditions. This paper summarizes and compares the general conclusions of recent works on evaluating the structural performance of RCC dams.
Keywords: Roller compacted concrete; dams; numerical analysis; finite element modeling; thermal stress; seismic behavior